Ensiklopedia Budaya Nusantara Berbasis Web - Purnomo Herianto; Yulia Yulia (Jurnal Infra, 2017)
Encyclopedia of the archipelago culture is a collection of information throughout the culture that existed in Indonesia before the independence of Indonesia in 1945. Culture is formed because of social circumstances in the community. The community performs daily habits and the habit is passed on from generation to generation so that it becomes a tradition. Archipelago has a variety of clothes, dance, house, song, and language. Each province has one culture that became the province's mascot, for example East Java has a joglo house. In this web based program contains cultural information that is easy to find. The end result of this cultural web program is to help people who want to know the culture of Indonesia and promote Indonesian culture in the virtual universe.